Pathogenetic Mechanisms of Hepatitis C Virus-Induced B-Cell Lymphomagenesis - Fabio Forghieri; Mario Luppi; Patrizia Barozzi; Rossana Maffei; Leonardo Potenza; Franco Narni; Roberto Marasca (Clinical and Developmental Immunology)
Hepatitis C virus (HCV) infection is probably the most common chronic viral infection and affects an estimated 180 million people worldwide, accounting for 3% of the global population. Although the liver is considered to be the primary target, extrahepatic manifestations are well recognized among patients with chronic HCV infection. Epidemiological studies have clearly demonstrated a correlation between chronic HCV infection and occurrence of B-cell non-Hodgkin's lymphomas (B-NHL). The clinical evidence that antiviral therapy has a significant role in the treatment at least of some HCV-associated lymphoproliferative disorders, especially indolent B-NHL, further supports the existence of an etiopathogenetic link. However, the mechanisms exploited by HCV to induce B-cell lymphoproliferation have so far not completely clarified. It is conceivable that different biological mechanisms, namely, chronic antigen stimulation, high-affinity interaction between HCV-E2 protein and its cellular receptors, direct HCV infection of B-cells, and “hit and run” transforming events, may be combined themselves and cooperate in a multifactorial model of HCV-associated lymphomagenesis.